University-Industry Linkage & Development of Higher Education: A Study about Faculty Perception - PRIYA, DR. ASHUTSOH; SAXENA, TULIKA; DWIVEDI, DR. RUCHI; VISHWAKARMA, KAMINI (The journal of contemporary issues in business and government, 2021)
Higher education in India has expanded enormously since independence and enlarged in size but, this enlarged size of the university campuses in India, is now facing financial crisis which is increasing more as visible in most of the developing countries. University industry linkage may be an alternative to this crisis. Establishing an effective & successful collaboration between universities and industries in order to remain competitive and financially viable is an alternative. But this relation will sustain if appropriate steps will be taken by both sides (Universities & industries) to benefit mutual interests with objective to serve the society. This paper makes an attempt to present the perception of higher education faculty members about the importance of University-Industry linkage and it is an effort to discuss the ways and means for making a strong university - industry linkage.